Urosepsis in adults - Lađević, Nebojša; Vuksanović, Aleksandar; Durutović, Otaš; Jovičić, Jelena; Lađević, Nikola; Likić Lađević, Ivana; Nešić, Dejan M.; Jovanović, Vesna (Archives of Biological Sciences, 2021)
Paper description: Urinary tract infections are a risk factor for urosepsis development, a severe complication that progresses rapidly. Common causes of urosepsis and information regarding the category of high-risk patients are provided. The increase in urinary tract infections with multiresistant bacteria is emphasized, especially in patients with recurrent urinary tract infections and their frequent treatment. These infections occur in patients with structural/functional malformations that interfere with urine flow. Urosepsis is caused by obstruction of the urinary tract; development of septic shock can often be prevented by early deopstruction. Early recognition of the focus of urosepsis in the urinary tract is imperative. Abstract: Urosepsis is defined as sepsis caused by urinary tract infection (UTI). Urosepsis represents a quarter of all cases of sepsis in adults. Complications of UTIs are the most common risk factor for urosepsis development. These infections, especially pyelonephritis, often occur in patients with structural or functional malformations that interfere with normal urine flow. The problem of a significant increase in UTIs with multiresistant bacteria should be emphasized, especially in patients with recurrent UTI and their frequent treatments. As the urogenital tract is one of the most common sources of infection in sepsis in general, a detailed assessment of the tract should be carried out in all septic patients. Even though urosepsis is associated with a relatively good prognosis and lower mortality than sepsis of another etiology, it occurs rapidly and progresses at a significant speed. Since urosepsis is mainly the result of obstruction of the urinary tract, the development of septic shock can most often be prevented by implementing early deobstruction. Knowledge of the most common causes of urosepsis and the category of high-risk patients will provide clinicians with the tools with which to prevent its occurrence.